Menari Tanpa Rasa: Pendidikan Kritis Anak Tunagrahita dalam Pembelajaran Seni Tari di SDLB Kuncup Bunga Denpasar - Ni Putu Diah Astriningsih; I Nyoman Suarka; I Gede Mudana (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
The importance of critical education for mentally retarded children in learning Balinese dance is related to learning, knowledge, and training for mentally retarded children. Critical education as an approach that can help marginalized mentally retarded children in obtaining dance learning to realize the social reality faced in education. Therefore,this article seeks to find out the relationship between critical education for mentally retarded children and the dance learning at the Denpasar Extraordinary Primary School of Kuncup Bunga. Critical education relations relate to the relationship of government stakeholders, teachers, communities, and parents of students who have power over mentally retarded children. The teacher considers mentally retarded children as weak children have unilaterally produced the most marginalized students in the Denpasar Kuncup Bunga Extraordinary Primary School.